Public-sector debt dynamics in Brazil - Afonso S. Bevilaqua; Rogério L. F. Werneck (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1997)
1. INTRODUCTION 2. POLICY MIX AND THE PUBLIC-SECTOR NET DEBT 3. SKELETONS IN THE CLOSET, PRIVATIZATION PROCEEDS AND SEIGNIORAGE 4. SIMULATING DEBT DYNAMICS 5. SENSITIVITY ANALYSIS 6. CONCLUDING REMARKS APPENDIX: THE SIMULATION MODEL
Keywords: 330